LETRAMENTO DIGITAL: INSERÇÕES TECNOLÓGICAS NO CONTEXTO FORMADOR DO PEDAGOGO - Conceição, Elizete de Fatima Veiga da (2020)
We are inserted in the digital age, of information and knowledge, which is less favoring manual labor and demanding more our ability to use the brain, human capacities to think, act, analyze and discern what is accessed through the WEB. Teaching in this age requires teachers to be prepared to develop digital literacy in the classroom. Thinking about the exposed context, this dissertation has as its theme the digital literacy from technological insertions in the pedagogue educational context. Like this, started by the following question-problem: how does the curriculum of a pedagogy course contemplate the study of digital information and communication technologies, and contributes to digital literacy in the initial training of a pedagogue? To this end, this study aims to analyze the curriculum of a pedagogy course with an emphasis on how the Digital Technologies of Information and Communication (DTIC) are used for the development of digital literacy in the formation of the future pedagogue. The methodology used was the qualitative, descriptive and transversal research, characterized as a case study, which used document analysis, questionnaires and content analysis as a way of acquiring knowledge. The documentary analysis included the study of the curriculum matrix of the pedagogy course; and the questionnaires, applied to students graduating from a pedagogy course, were conducted with open questions, and were completed without the interference of the researcher. For data analysis, the content analysis technique proposed by Bardin (2016) was used. In this analysis, it was found that the pedagogy course offers to the students, in its curricular matrix, a specific mandatory subject for the teaching of technologies, but also offers an optional subject that involves the use of technologies. It was also highlighted that most of the subjects offered during the course use digital technologies in the classroom. The students have access to the Wi-Fi network and the Moodle tool, however it is being used only as a content repository. With regard to the students' understanding of the concept of digital literacy, they are not far from what is defended by the authors who support the study, a concept defined by the social practices of reading and writing developed in digital environments and which also include critical analysis of what is accessed. However, despite claiming that their experiences with technologies in the course were significant, most students still do not feel secure in developing digital literacy in their future classroom practices. It follows that digital literacy is being worked on in the analyzed pedagogy course, as the course includes technological insertions necessary to develop digital literacy, but it is not complete without human action, that is, students are also responsible agents for that digital literacy happens fully.